Self‒assembled core‒shell structured Si@CuO energetic materials for enhanced exothermic performance. (November 2019) - Wang, Qihui; Yang, Shengbo; Bao, Hebin; Wang, Qianyu; Li, Xueming; Yang, Wenjing
Abstract: Si is considered as a promising fuel for energetic materials and has received increasing attention. In this study, a novel core‒shell structure Si@CuO energetic material was successfully synthesized by self‒assembly method. Poly(4‒vinylpyridine) was used as cross linker to coat nano‒CuO on the surface of nano‒Si to form core‒shell structure Si@CuO energetic material. The morphology and composition of the nano‒Si, nano‒CuO and Si@CuO energetic materials were investigated in detail by scanning electron microscopy, transmission electron microscopy and X‒ray diffraction. The results demonstrate that the maximum actual heat release of Si@CuO with core‒shell structure is 1061.4 J/g when the equivalent ratio is 1.0, which is greater than 532.8 J/g of Si/CuO energetic materials prepared by ultrasonic mixing method. These results provide a helpful and practical strategy for the preparation of energetic materials with long‒term storage stability. Highlights: Si@CuO energetic materials were successfully synthesized by self‒assembly method. The core‒shell Si@CuO shortens the distance between nano‒Si and nano‒CuO. Prepared Si@CuO energetic materials exhibited excellent exothermic performance.